Assaults during Lockdown in NSW and Victoria - Solmaz Moslehi; Jaai Parasnis; Massimiliano Tani; Josephina Vejayaratnam (Institute of Labor Economics (IZA), 2021)
We study the relationship between Covid-19 lockdowns and domestic assaults in New South Wales and Victoria using police data on crime by Local Government Area over the period 2019-2020. We apply both Ordinary Least Squares and a fixed effect estimator, and find that domestic assaults decline during the lockdowns of 2020, but less than other types of assaults. As a result, there is a higher relative incidence of domestic assaults rather than an overall increase in crime. The results are robust to omitted variable bias based on Oster's (2019) test, and mimic Boman and Gallupe (2020) - a similar study carried out in the US.
Keywords: I10; K42; 330; domestic assault; COVID-19; lockdowns; crime